Patient Demographics and Major Adverse Cardiovascular Events after Androgen Deprivation Therapy for Prostate Cancer - Christopher J. D. Wallis; Kevin C. Chen; Stuart Atkinson; Deborah M. Boldt-Houle (Advances in Urology)
Background. The association between patient demographics and CV events after ADT using real-world data was evaluated. In addition to encompassing >30 times more patients than all previous MACE studies, this is the first study, to the best of our knowledge, to include a comprehensive listing of many demographic factors from one large, recent US dataset over a long period of time. Materials and Methods. The retrospective analysis of data in the Decision Resources Group (now Clarivate) Real World Evidence repository, representing >300M US patients from 1991 to 2020 across all US regions, was performed. Patients with PCa receiving ≥1 ADT injection were included. MACE risk after ADT initiation was evaluated for demographic and potential PCa-related risk factors. Kaplan–Meier survival curves were constructed, and Cox regression was used to evaluate the association between MACE risk and demographic/PCa-related risk factors. Results. Overall, MACE risk was slightly lower in the first year after ADT initiation (3.9%) vs. years 2–4 (∼5.2%). In a multivariate Cox model, MACE risk after ADT initiation was significantly higher for older vs. younger patients (adjusted HR per increasing year = 1.08, 95% CI: 1.07–1.09), men with a history of MACE vs. without (HR = 2.22, 95% CI: 1.72–2.88), men with very low BMI vs. normal or high BMI (HR for decreasing BMI per kg/m2 = 1.02, 95% CI: 1.01–1.03), White vs. Black patients (HR = 1.30, 95% CI: 1.08–1.55), and patients who did not use statins vs. those who did (HR = 1.13, 95% CI: 1.00–1.27). Of the PCa-related risk factors, MACE risk after ADT initiation was significantly higher for oncology vs. urology treatment setting (HR = 2.47, 95% CI: 2.12–2.88), patients with baseline metastasis vs. those without (HR = 2.30, 95% CI: 1.72–3.07), and patients treated with antagonists vs. agonists (HR = 1.62, 95% CI: 1.25–2.10). Conclusions. Demographic factors are important contributors to increased MACE risk for men with PCa on ADT. Clinicians should monitor risk factors and modify if possible.